PENGARUH STRATEGI ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA UMKM (STUDI PADA UMKM GULA MERAH DI KECAMATAN PEGAJAHAN KABUPATEN SERDANG BEDAGAI). - Dicky Husein Maulana Purba; Aswin Fahmi D (INTERNATIONAL, Journal of Sharia Business Management, 2023)
MSMEs are one of the pillars of a country's economy, including SMEs from Indonesia. Brown Sugar MSMEs in Pegajahan Village are one of the MSMEs in Pegajahan District, Serdang Bedagai Regency. This research aims to analyze the influence of market orientation and product innovation variables on MSME performance simultaneously and partially. The type of research used is explanatory research with a quantitative approach. The sample in this study was 34 respondents, namely brown sugar MSME owners in Pegajahan Village. The sampling technique in this research uses non-probability sampling, a total (saturated) sampling type because all members of the population are used as samples. The data collection method uses a questionnaire. Data analysis uses descriptive analysis and multiple linear regression analysis. The results of multiple linear regression analysis show that market orientation (X1) has an influence, but is not significant, on the performance of MSMEs (Y) as indicated by a probability value (sig) of 0.742 > 0.1. Meanwhile, the product innovation variable (X2) has a significant effect on performance (Y) as indicated by a probability value (sig) of 0.098 < 0.1. Market Orientation (X1) and Product Innovation (X2) have a joint influence on MSME performance (Y) with an R2 value of 17%.